2012
DOI: 10.1002/uog.11161
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic predictors of surgery in fetal coarctation of the aorta

Abstract: Objectives 22.4 (range. 16.6-7.0) weeks and the median number of scans per fetus was three (range, one to five). I < −2 at final scan was the most powerful predictor (odds ratio, 3.6 (95% CI,). Shelf was identified in 66% and Flow in 50% of fetuses with CoA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
74
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(92 citation statements)
references
References 16 publications
10
74
0
4
Order By: Relevance
“…The reference ranges for cardiac outflow tracts and z scores presented in this study can be applied in the assessment of patients with cardiac asymmetry, pulmonary stenosis, right ventricular outflow tract obstruction, or aortic stenosis 2,3,5,10,11,13,15,16,18,[24][25][26][27][28][29][30][31][32] ; in these cases knowledge of the accurate z score can aid in predicting the need for neonatal intervention and to plan perinatal management. Z scores may also be useful in forecasting the natural history of valve stenosis and in designing clinical trials on the value of in utero valvuloplasty, where patients can be stratified according to z scores.…”
Section: Potential Rhythm Disturbance 90mentioning
confidence: 99%
“…The reference ranges for cardiac outflow tracts and z scores presented in this study can be applied in the assessment of patients with cardiac asymmetry, pulmonary stenosis, right ventricular outflow tract obstruction, or aortic stenosis 2,3,5,10,11,13,15,16,18,[24][25][26][27][28][29][30][31][32] ; in these cases knowledge of the accurate z score can aid in predicting the need for neonatal intervention and to plan perinatal management. Z scores may also be useful in forecasting the natural history of valve stenosis and in designing clinical trials on the value of in utero valvuloplasty, where patients can be stratified according to z scores.…”
Section: Potential Rhythm Disturbance 90mentioning
confidence: 99%
“…On the contrary, CoAo in fetal life is often considered a ‘uniform' condition in which only the diagnosis of ‘suspicion' can be made, and most cases usually undergo the same management pathway, thus not giving the parents individualized information regarding the more likely outcome for their fetus [38,39]. Recent studies have shown a relationship between prenatally measured Z-score of the aortic isthmus and the likelihood of surgery in suspected CoAo [19,20]. We have moved forward with this study showing firstly that patients with prenatally suspected CoAo requiring median sternotomy for CoAo repair have significantly smaller Z-score values of the aortic isthmus in sagittal view when compared with those who are repaired through left thoracotomy, and secondly that following two-step assessment, in fetuses in whom detailed echocardiography has previously showed that have the higher risk of truly having CoAo, this single parameter may be applied prenatally to predict their more likely surgical approach for CoAo repair with a high degree of accuracy (sensitivity of 78% and specificity of 82% for predicting sternotomy approach).…”
Section: Discussionmentioning
confidence: 99%
“…Recent papers have shown that some direct size-based and functional fetal echocardiographic parameters may be useful to predict better the likelihood that CoAo will be confirmed or not postnatally [19,20,21], but the prediction of the more likely surgical approach for CoAo is rarely aimed prenatally. This study evaluates the capacity of fetal echocardiography to predict this important issue.…”
Section: Introductionmentioning
confidence: 99%
“…Diagnostic accuracy may be improved by means of combining size-based cardiac parameters with gestational age at diagnosis [10]. Flow disturbance at the isthmus is considered as one of the qualitative diagnostic features of CoAo in the fetuses [6,9,10]. It is known description of flow disturbance as a delayed flow through aortic isthmus.…”
Section: Prenatal Predictionmentioning
confidence: 99%
“…Currently prenatal diagnosis of this condition lacks sensitivity at screening and specificity even when performed by experts in tertiary centers. This leads to increased morbidity and mortality in affected neonates without correct prenatal diagnosis, who often collapse and require resuscitation before surgery [2,4,5] and unjustified costs of cardiac centers due to false-positive cases [6]. Despite advances in fetal echocardiography and the description of antenatal findings associated with neonatal CoAo, this lesion remains the most challenging diagnosis to be made in fetal and early neonatal life [6][7][8][9][10].To the best of our knowledge quantitative fetal Doppler criteria of neonatal CoAo have not been described in the literature.…”
Section: Introductionmentioning
confidence: 99%